Vol up / Muhamad Arif Affandi Ami Ardi - Ami Ardi, Muhamad Arif Affandi (Universiti Teknologi MARA, Kedah, 2025)
Vol Up is an innovative culinary venture established to cater to Malaysia's ever growing love for spicy food. Rooted in the cultural affinity for bold and fiery flavors, VolUp introduces a revolutionary line of spicy chicken with three customizable levels of heat: Level 1 (Mild ), Level 2 (Spicy), and Level 3 (Extra). Malaysia's passion for spicy food is undeniable, with the country ranking 11th globally in per capita spice consumption, averaging 5.57 kilograms per person annually, and 15th in total spice consumption, with 187,000 metric tons consumed in 2021. This cultural love for fiery flavors is further evidenced by the massive popularity of McDonald's spicy chicken offerings. For instance, during a Malaysia Day promotion in 2024, McDonald's Malaysia sold over 700,000 pieces of fried chicken in a single day. Such statistics underscore a thriving demand for high quality spicy products in the fast-food industry, inspiring VolUp to create an unforgettable dining experience for spice enthusiasts. At VolUp, our spicy chicken isn't just food, it 's a sensory adventure designed to delight and challenge all levels of spice tolerance. Each level of heat is carefully crafted using a proprietary blend of premium ingredients and spices, ensuring exceptional flavor profiles at every stage. Whether it's the approachable warmth of Level l, the exciting kick of Level 2, or the fiery thrill of Level 3, VolUp offers a truly customizable culinary journey. VolUp's mission is to elevate the dining experience by turning spiciness into on art form while honoring Malaysia 's deeply rooted love for intense flavors. By topping into this culturally significant market and delivering a product that appeals to the mosses, VolUp is poised to make a fiery and lasting impact in the Malaysian food scene, setting a new standard for the fa st food industry and solidifying its place as a staple for spice lovers across the country.